ANALISIS MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DI PERBANKAN SYARIAH TAHUN 2018-2021 - Winamida Damaris, Marcelin; Linawati; Solikah, Mar'atus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to determine the effect of the board of directors, board of commissioners, independent board of commissioners, sharia supervisory board, and audit committee on financial performance partially in Islamic banking registered with the Financial Services Authority from 2018 to 2021. This type of research is quantitative with data analysis techniques using multiple linear regression analysis assisted by SPSS for windows version 25. Sample selection using purposive sampling method. Data collection using the documentation method. The results of this study indicate that the board of directors, board of commissioners, independent board of commissioners, sharia supervisory board, and audit committee partially has no effect on financial performance. The novelty of this study uses the 2018-2021 observation year period, and uses the variables of the board of directors, board of commissioners, independent board of commissioners, Sharia supervisory board, and audit committee.